A new species of Elachistocleis (Anura: Microhylidae) from the Brazilian Pantanal - Alessandher Piva (Phyllomedusa: Journal of Herpetology, 2017)
A new species of Elachistocleis from the Brazilian Pantanal is described. The new species differs from all other Elachistocleis in having the following combination of characters: medium to large-sized species (26.9–40.3 mm); head length about 89% of head width; post-commissural gland poorly developed; dorsum in preservative (EtOH 70%) slightly rough, grayish, with minute, scattered white dots and a large, elongated dark gray spot on the mid-dorsum and posterior part of head; venter gray or brown with white spots separating dorsal and ventral regions; a single vocal sac dark gray; large, irregular, light cream spot on humerus; large, irregular light cream spots on groin; light cream, irregular stripe on posterior surfaces of thighs; and irregular, light cream spots on the proximal internal surface of each shank. This new species increases the number of Oval frogs for the state of Mato Grosso do Sul to four and demonstrates the value of the single protected area in Corumbá for biodiversity conservation. Continuing field investigations in the Maciço do Urucum are necessary to determine the diversity of the herpetofauna in that region.